Lipopolysaccharide-Activated Bone Marrow-Derived Dendritic Cells Suppress Allergic Airway Inflammation by Ameliorating the Immune Microenvironment - Min, Zhihui; Zeng, Yuzhen; Zhu, Tao; Cui, Bo; Mao, Ruolin; Jin, Meiling; Chen, Zhihong (Frontiers in Immunology, 2021)
Background Previous studies have shown that lipopolysaccharide (LPS)-activated bone marrow-derived dendritic cells (DClps) might induce tolerance in autoimmune and cancer models in vivo, whereas it remains unclear whether DClps could play a role in allergic disease model. Herein, we aimed to elucidate the potential effects of DClps on OVA-sensitized/challenged airway inflammation in a mouse model, which may help facilitate the application of specific tolerogenic dendritic cells (tolDC) in allergic asthma in the future. Methods The phenotype and function of immature DC (DCia), DClps or IL-10-activated-DC (DC10) were determined. OVA-sensitized/challenged mice were treated with OVA-pulsed DCia or DClps or DC10. We assessed the changes of histopathology, serum total IgE level, pulmonary signal transducers and activators of transcription (STAT), pulmonary regulatory T cells (Tregs), and airway recall responses to OVA rechallenge, including proliferation and cytokine secretory function of pulmonary memory CD4+ T cells in the treated mice. Results DClps exhibited low levels of CD80 and MHCII and increased levels of anti-inflammatory cytokines such as IL-10 and TGF-β. Additionally, DClps treatment dramatically diminished infiltration of inflammatory cells, eosinophilia, serum IgE and STAT6 phosphorylation level, increased the number of pulmonary Tregs. In addition, DClps treatment decreased the proliferation of pulmonary memory CD4+ T cells, which further rendered the downregulation of Th2 cytokines in vitro. Conclusion LPS stimulation may lead to a tolerogenic phenotype on DC, and thereby alleviated the Th2 immune response of asthmatic mice, possibly by secreting anti-inflammatory cytokines, inhibiting pulmonary memory CD4+ T cells, downregulating pulmonary STAT6 phosphorylation level and increasing pulmonary Tregs.